The effectiveness of computer based learning - Underwood, Jean (1987)
Is the innovation of educational computing likely to be effective in facilitating the development of children's minds? The research reported in this thesis approached the question by investigating two issues related to the introduction of classroom computers. Firstly, is the educational environment receptive to the new technology, and secondly, can computer-based learning make significant changes in the development of children's cognitive ability?